Armed actor interventions in humanitarian and public health crises: examining perspectives of crisis-affected community members - Samuel T. Boland; Alexandria Nylen; Madison Bates; Maria Carinnes Alejandria; Rob Grace; Zein Tayyeb; Adam C. Levine (Conflict and Health, 2024)
Abstract Background Despite frequently providing non-military services in times of crisis, little systematic research has examined the perspectives of crisis-affected community members on the role of armed actors responding to humanitarian crises and public health emergencies. Methods To address this research gap, 175 interviews were conducted (2020–2021) amongst humanitarian and public health practitioners; armed actors; and crisis-affected community members across three country and four crisis contexts. Specifically, this effort included an Ebola outbreak in the Democratic Republic of the Congo; a refugee crisis on the Jordanian-Syrian border; and a volcanic eruption and COVID-19 outbreak in the Philippines. Data was analysed using grounded theory principles. Results Crisis-affected community members held diverse views. Non-state armed groups (NSAGs) and government armed actors were characterised as antagonists by some but supportive by others; gender issues were central to perceptions of armed actors, in ways that were both prejudicing and favourable. Overall perception was most closely linked to armed actor roles rather than the relative amount of conflict in a given area. Conclusions Findings nuance the relevant literature characterizing NSAGs as disruptive agents, and also the relevant literature that does not fully consider the nuances of gender and armed actor roles as deeply relevant to crisis-affected community perspectives on armed actors. These findings have important implications for both policy and academic discourse on militarization and localization.